Automated Web Application Testing Using Improvement Selenium - Sharifah Anis Syed Naser, Sharifah Anis (Universiti Teknologi PETRONAS, 2012)
The basis of this project is to develop an automated web application testing tool using the enhancement of Selenium which is an open source testing tool. The tool should able to handle automated tests with a group of testers. The current testing tools are proprietary tool and not all test engineers expert or have a deep knowledge in programming which is required to create automated test case. The main problem in testing is time consuming where some of testers are still using manual testing. The scope of study is to develop a tool for software tester who focuses on functional testing and the tool can execute test cases on different platforms which are Windows, Linux and Mac. Each platform has different browsers which are Firefox, Internet Explorer and Chrome. A qualitative research is done in this project by interviewing several software test engineers who are familiar with automated testing and a framework has been designed in order to fulfill the requirements and to cater the problems that are currently facing. This framework is developed and coded by using Eclipse IDE, Apache ANT and TestNG. As a result, this testing tool is using the combination of Selenium Grid and TestNG in order to create a template for software tester to use it easily. This framework is compatible to all browsers and platforms that are commonly used by Internet users.